Effect of Braking Conditions on Wear Loss of the Disc Drake Pad - Zhao Xiaohui; Huan Kaixuan; Zhang Zhijie; Yang Wenbin; Hu Sheng (Jixie chuandong, 2024)
The brake pad is one of the most critical safety part in the braking system, and it plays a vital role in ensuring drivers safety. In order to investigate the effect of braking conditions on the wear loss of disc brake pads, using Ansys Workbench simulation software, the wear simulation model was built based on the Archard wear model; Archard wear commands were added through the APDL command flow to realize the wear simulation of the brake pad, so as to analyze and calculate the wear loss of the brake pad. The brake pad friction and wear test bench was built and five groups of different braking conditions were randomly selected for brake pad wear test, and the test results were compared and analyzed with the simulation results to verify the correctness of the simulation model. The results show that within the set parameter range, the effect of the brake pressure on the wear loss of brake pad is smaller compared to the effect of the initial brake speed; without the intervention of the external heat source, the individual effect of the brake pad surface temperature on the wear loss is smaller compared to the combined effect of other parameters such as initial brake speed and brake pressure on the wear loss of the brake pad.